Tinjauan Hukum Islam terhadap Suami yang Tidak Memberikan Nafkah kepada Istri yang Bekerja: Studi di Lingkungan Aek Tapa, Kelurahan Bakaran Batu, Kecamatan Rantau Selatan - Rahmadani, Laila; Hasanah, Uswatun (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The phenomenon of wives replacing the husband's role in earning a living in the family occurs in Aek Tapa Neighborhood, Bakaran Batu Village, South Rantau Subdistrict. The wives are forced to work to meet household needs because their husbands are not responsible for fulfilling their livelihoods. The purpose of this study is to find out the factors that cause wives to work for a living, and to find out the review of Islamic law on husbands who do not provide maintenance to working wives. The research method used by the author in this research is qualitative with an empirical approach. Primary sources are interviews with wives who play a role in earning a living and secondarysources are obtained from books, related literature and relevant articles of legislation. The results of this study conclude: One of the factors of wives working for a living is due to economic needs. Islamic Law Review of husbands who do not provide maintenance to working wives, namely a husband who does not provide maintenance for his wife on the grounds that the wife also helps earn a living, the husband is still obliged to provide for his wife and maintenance remains an absolute right for the wife even though the wife helps earn a living with the husband's permission.